Penerapan Sistem Enterprise Resource Planning Modul Sales pada Toko Bangunan Harapan Maju Menggunakan Odoo - Diah Dewi Lestari; Lufty Abdillah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Toko Bangunan Harapan Maju is a medium-sized business that sells various kinds of construction equipment and materials and also located on Tipar Cakung Sukapura street. The problem at Toko Bangunan Harapan Maju is that sales reporting is recorded manually, namely by recording it on a ledger so that the running system still has shortcomings such as duplicate data or data that has not been written and data errors. This research aims to create a sales system that can help the Harapan Maju Building Shop to facilitate transactions and data reporting. The results of this study are the implementation of the ERP system using the Odoo application in the sales module with the ASAP method which has been adjusted to the needs and business processes of the product sales department.